Career expectations and satisfaction among Malaysian dentists with expanded roles at government dental specialist clinic - Ab Malek, Azizi; Mohd Radzi, Nawwal Alwani; Che Musa, Muhd Firdaus (2022)
Introduction: Public dentists in Malaysia undergoing attachment at the Ministry of Health (MOH) Dental Specialist Clinic (DSC) hold enhanced skills that enable them to treat cases of intermediate complexity. Public dentists interested in pursuing post-graduate studies for career advancement were required to complete a period of clinical attachment at selected MOH DSCs. Objectives: This cross-sectional study aimed to explore dentists' expanded roles, career expectations and satisfactions at the MOH DSC. Methods: A total of 208 dentists from DSC nationwide completed an online questionnaire in June 2022. Demographic data and information on dentists' expanded roles were retrieved. Responses on dentists' career expectations and satisfaction were collected using a 5-point ordinal scale. Associations between sociodemographic and other variables were determined using the chi-square, independent t-test and ANOVA (p<0.05). Results: The mean age of the respondents was 32.68 ± 2.48. Almost half (49%) of the respondents were attached to a non-hospital-based clinic. 71% of the dentist was permanently attached at the DSC, while 21% were attached temporarily at the DSC. Permanently-attached dentists had significantly higher career expectations mean scores of 24.5 ± 5 compared to partially-attached dentists (27.2 ± 7) (p = 0.004). Dentists attached at a non-hospital-based clinic (p=0.046), working with more than 15 years of experience (p=0.013) and 12-18 months of attachment (p=0.014), had higher career satisfaction. Multiple logistics regression analysis revealed that non-Malay (OR=1.54; p=0.035) and those who applied for scholarships more than three times (OR=1.85; p=0.050) had a higher satisfaction level. In contrast, the duration of attachment at DSC of more than 19 months contributed to a lower career satisfaction level (OR=0.44; p=0.029). Conclusions: Dentists at DSC, MOH demonstrated diverse career expectations and satisfaction levels despite working under a similar organizational structure. Dentists' ethnicity, duration of attachment, workplace and frequency of applying for scholarships influenced their career expectations and satisfaction.